Modified fischer-tropsch synthesis: A review of highly selective catalysts for yielding olefins and higher hydrocarbons - Tavares, Marlon; Westphalen, Gisele; Araujo Ribeiro de Almeida, João Monnerat; Romano, Pedro Nothaft; Sousa-Aguiar, Eduardo Falabella (Frontiers in Nanotechnology, 2022)
Global warming, fossil fuel depletion, climate change, as well as a sudden increase in fuel price have motivated scientists to search for methods of storage and reduction of greenhouse gases, especially CO2. Therefore, the conversion of CO2 by hydrogenation into higher hydrocarbons through the modified Fischer–Tropsch Synthesis (FTS) has become an important topic of current research and will be discussed in this review. In this process, CO2 is converted into carbon monoxide by the reverse water-gas-shift reaction, which subsequently follows the regular FTS pathway for hydrocarbon formation. Generally, the nature of the catalyst is the main factor significantly influencing product selectivity and activity. Thus, a detailed discussion will focus on recent developments in Fe-based, Co-based, and bimetallic catalysts in this review. Moreover, the effects of adding promoters such as K, Na, or Mn on the performance of catalysts concerning the selectivity of olefins and higher hydrocarbons are assessed.